Methodology for drought impacts management in developing countries - Traoré, Zan N'Tio, author; Fontane, Darrell G., advisor; Gates, Timothy, committee member; Smith, Freeman M., committee member; Grigg, Neil S., committee member (Colorado State University. Libraries, 2005)
Droughts are occurring in many regions of the world with increased frequency and severity. Due to the recurrence and persistence of their impacts, the strategy of crisis intervention for mitigation has shown its limits. To deal not only with the immediate effects, but also with the long-term drought impacts, researchers have recommended new strategies, which are more proactive and comprehensive. Among other strategies suggested, contingency planning is one that has been adopted as a standard method of preparing for, and managing drought impacts. To this end, different planning frameworks have been proposed to drought stricken countries and places. Capitalizing on the proposed planning frameworks, many states in the USA and other countries have defined their contingency plans for drought impacts management. However, a review of some of the existing plans evidences the need to address such critical issues as: The sustainability of the water resources system under consideration with respect to the demands, drought impacts and other climatic and environmental changes; The selection of the management options most relevant to conflicting management objectives in a developing drought; The definition of the timing and sequencing of the implementation of the selected management actions in order to achieve the optimal mitigation; The integration of the immediate objectives of drought impacts management with the strategic objectives of water resources management. This study proposes procedures for assessing the sustainability of water resources system and for integrating the strategic, tactical and emergency objectives of drought impacts management. A Multicriteria Decision-Analysis (MCDA) model is developed and used as tool of integration, which helps identify the timing and sequencing of the alternatives actions most relevant to the management objectives. Water resources managers may use the model in the preliminary phase of drought impacts management planning or as tool for implementing a drought plan. Two methods proposed by the Delft Hydraulic Laboratory in the Netherlands (ASCE, 1998) for sustainability assessment are applied. One is the Weighted Statistical Indices method to be applied to the river system. For the second method, the MCDA model uses a modified version of the Weighted Criteria Indices method for assessing the relevance and sustainability of alternative options available for drought impacts management.
Keywords: civil engineering; environmental science